Ergolytic/Ergogenic Effects of Creatine on Aerobic Power - Smith, A. E.; Fukuda, D. H.; Ryan, E. D.; Kendall, K. L.; Cramer, J. T.; Stout, J. (International Journal of Sports Medicine, 2011)
This study evaluated the effects of creatine (Cr) loading and sex differences on aerobic running performance. 27 men (mean±SD; age: 22.2±3.1 years, ht: 179.5±8.7 cm, wt: 78.0±9.8 kg) and 28 women (age: 21.2±2.1 years, ht: 166.0±5.8 cm, wt: 63.4±8.9 kg) were randomly assigned to either creatine (Cr, di-creatine citrate; n=27) or a placebo (PL; n=28) group, ingesting 1 packet 4 times daily (total of 20 g/day) for 5 days. Aerobic power (maximal oxygen consumption: VO2max) was assessed before and after supplementation using open circuit spirometry (Parvo-Medics) during graded exercise tests on a treadmill. 4 high-speed runs to exhaustion were conducted at 110, 105, 100, and 90% of peak velocity to determine critical velocity (CV). Distances achieved were plotted over times-to-exhaustion and linear regression was used to determine the slopes (critical velocity, CV) assessing aerobic performance. The results indicated that Cr loading did not positively or negatively influence VO2max, CV, time to exhaustion or body mass (p>0.05). These results suggest Cr supplementation may be used in aerobic running activities without detriments to performance.
Keywords: gender; body-weight activity; supplement; anaerobic